2021
DOI: 10.1186/s12879-021-06045-3
|View full text |Cite|
|
Sign up to set email alerts
|

Methylprednisolone or dexamethasone, which one is superior corticosteroid in the treatment of hospitalized COVID-19 patients: a triple-blinded randomized controlled trial

Abstract: Background Although almost a year has passed since the Coronavirus disease 2019 (COVID-19) outbreak and promising reports of vaccines have been presented, we still have a long way until these measures are available for all. Furthermore, the most appropriate corticosteroid and dose in the treatment of COVID-19 have remained uncertain. We conducted a study to assess the effectiveness of methylprednisolone treatment versus dexamethasone for hospitalized COVID-19 patients. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
243
4
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(262 citation statements)
references
References 39 publications
8
243
4
7
Order By: Relevance
“…Because the rationale for using dexamethasone is clear, many studies using other steroids have not been done. However recent studies have shown that methylprednisolone is not inferior to using dexamethasone [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the rationale for using dexamethasone is clear, many studies using other steroids have not been done. However recent studies have shown that methylprednisolone is not inferior to using dexamethasone [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RECOVERY trial is a large-scale, prospective, well-designed study, which demonstrated that the use of dexamethasone reduces mortality in patients with severe COVID-19 [ 11 ]. Other types of corticosteroids, such as hydrocortisone [ 19 ], have also been demonstrated to improve clinical outcomes [ 20 ]. The use of corticosteroids could theoretically cause several side effects [ 21 ], but did not inhibit secondary bacterial infection or viral clearance [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed doses for methylprednisolone are 1-2 mg/kg, followed by the same daily dose at an infusion rate of 10 ml/h daily with a gradual taper in this setting (Meduri et al, 2018;Villar et al, 2020). Another study supported that methylprednisolone at 2 mg/kg is superior than dexamethasone at 6 mg/kg with lower MV and reduced hospital stay due to hypothesized higher lung tissue-to-plasma ratios in methylprednisolone (Ranjbar et al, 2021). An individual patient analysis investigating corticosteroid use on early and late ARDS demonstrated improved survival and a decreased duration of MV (Meduri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Current data supports the use of both IVIG and corticosteroids in all three categories of MIS-C. Dexamethasone has been used as an adjunctive treatment for hospitalized patients with active COVID-19 infection with prominent respiratory features and/or shock; however, methylprednisolone is more commonly used for MIS-C. A recently-published randomized controlled trial and retrospective trials suggest superiority of methylprednisolone over dexamethasone for acute/respiratory COVID-19 [ 51 , 52 ]. We would recommend use of methylprednisolone in all cases of MIS-C, unless there is a high index of suspicion for concomitant infection or if steroids are contraindicated.…”
Section: Introductionmentioning
confidence: 96%